Delusions of technical alien control: a phenomenological description of three cases - Hirjak, Dusan; Fuchs, Thomas (Psychopathology, 2010)
Background: A considerable number of schizophrenic patients develop delusions of technical alien control. In such cases, patients experience their thoughts, movements and feelings to be controlled by mysterious machines and contemporary technologies such as computers, the internet, X-rays and lasers. Methods: In this paper, we describe 3 cases of patients with disorders of self-experience and schizophrenic delusions involving a controlling technical device. We also analyse case reports from historical and modern psychiatric literature which describe ‘influencing machines’ and similar phenomena. Results: Of the 3 patients analysed, all complained of being controlled and impaired by some form of contemporary technology. Moreover, the presented cases illustrate psychopathological phenomena such as self-centrality, loss of ego boundaries, subjectification of perception, ‘paradoxes of delusions’, morbid objectification and loss of the sense of agency. Conclusion: Delusions of technical alien control and influencing machines constitute a characteristic form of delusional ideation in schizophrenic patients. They may be preceded by prodromal schizophrenic alterations such as disembodiment, alienation and reification of self-experience, depersonalization, derealization and bodily hallucinations. We propose that these prior experiences, especially if technically reifying in nature, may give rise to the phenomenon of technical delusions, thus expressing a particular affinity of basic self-experience in schizophrenia to modern technology. This is also consistent with the pathoplasticity hypothesis.
Published online: January 9, 2010
Gesehen am 15.05.2023